Tourism for whom?: Different paths to development and alternative experiments in Brazil - Bartholo, Roberto; Delamaro, Mauricio Cesar [UNESP]; Bursztyn, Ivan; Hallewell, Laurence (SAGE Publications, 2008)
The tourism policies pursued by the Brazilian government since the 1990s have not produced the benefits that were expected from mass tourism. The example of two very successful cases of community-based tourism, stressing paths rooted in a development model that is fair and environmentally responsible, shows that tourism development can improve the quality of life in communities that receive an influx of tourists provided that the local community is taken into account and the planning and implementation of such development focus on creating opportunities and benefits for its members. © 2008 Latin American Perpectives.
Keywords: Community-based tourism; Development; Government tourism policy; Prainha do Canto Verde; Silves; Tourism; policy implementation; policy making; quality of life; tourism development; Brazil; South America